Psychological Stress in Heart Failure: A Potentially Actionable Disease Modifier - Harris, Kristie M. (Heart Fail Rev, 2020)
Psychological stress is common in patients with heart failure, due in part to the complexities of effective disease self-management and progressively worsening functional limitations, including frequent symptom exacerbations and hospitalizations. Emerging evidence suggests that heart failure patients who experience higher levels of stress may have a more burdensome disease course, with diminished quality of life and increased risk for adverse events, and that multiple behavioral and pathophysiological pathways are involved. Furthermore, the reduced quality of life associated with heart failure can serve as a life stressor for many patients. The purpose of this review is to summarize the current state of the science concerning psychological stress in patients with heart failure and to discuss potential pathways responsible for the observed effects. Key knowledge gaps are also outlined, including the need to understand patterns of exposure to various heart failure-related and daily life stressors and their associated effects on heart failure symptoms and pathophysiology, to identify patient subgroups at increased risk for stress exposure and disease-related consequences, and the effect of stress specifically for patients who have heart failure with preserved ejection fraction. Stress is a potentially modifiable factor, and addressing these gaps and advancing the science of stress in heart failure is likely to yield important insights about actionable pathways for improving patient quality of life and outcomes.